Influence of local scour on the dynamic responses of OWTs under wind-wave loads - Yao, Yong; Rao, Mumin; Yu, Chi; Wu, Zhichao; Zhang, Cheng; Wu, Tianyu (Frontiers in Marine Science, 2024)
Offshore wind turbines (OWTs) often operate in complex marine environments, where they are not only subjected to wind and wave loads, but also adversely affected by scour. Therefore, it is of great significance to explore the effect of scour on the dynamic responses of OWTs under external loads to ensure structural safety, improve performance, and extend service life. In this study, a comprehensive numerical model of a 5-MW OWT, including tower, monopile, and soil-structure interaction (SSI) systems, is established by using ABAQUS platform. Aerodynamic loads is generated using blade element momentum, while wave loads is generated using the P-M spectral. The depth of scour is obtained based on on-site measured data. A comparative analysis is conducted between fixed foundations and SSI systems when conducting dynamic response analysis of OWTs under wave loads. Subsequently, the effect of scour on dynamic responses of OWTs under aerodynamic and wave loads is investigated. Results demonstrate that SSI can significantly influence the natural frequency and dynamic responses of the OWT. Therefore, it is essential to thoroughly consider SSI when evaluating the dynamic response of the OWT with local scour. The tower-top displacement and acceleration of the OWT with show a significant increasing trend compared to the non-scoured OWT. An increase in scour depth leads to higher maximum stress and stress amplitude in the steel monopile, which could potentially cause fatigue issues and should be given due attention.